Morphometric fruit traits of plants on Kilimanjaro - Maximilian Vollstaedt; Matthias Schleuning; Katrin Böhning-Gaese (PANGAEA, 2018)
This dataset includes morphological trait measurements of all plant species recorded on the study sites of Mt. Kilimanjaro. We measured traits related to size and supply of the fruits. For instance, the size and shape of a fruit determines which species may successfully exploit it. Additionally, the forest stratum in which plants display their fruits will attract a specific range of species. The data was collected in the field from 3 individuals for each species.
In supplement to: Vollstaedt, Maximilian; Ferger, Stefan W; Hemp, Andreas; Howell, Kim M; Töpfer, T; Böhning-Gaese, Katrin; Schleuning, Matthias (2017): Direct and indirect effects of climate, human disturbance and plant traits on avian functional diversity. Global Ecology and Biogeography, 26(8), 963-972, https://doi.org/10.1111/geb.12606